2019
DOI: 10.1590/1678-4685-gmb-2019-0151
|View full text |Cite
|
Sign up to set email alerts
|

Non-random distribution of microsatellite motifs and (TTAGGG)n repeats in the monkey frog Pithecopus rusticus (Anura, Phyllomedusidae) karyotype

Abstract: The monkey frog, Pithecopus rusticus (Anura, Phyllomedusidae) is endemic to the grasslands of the Araucarias Plateau, southern Brazil. This species is known only from a small population found at the type locality. Here, we analyzed for the first time the chromosomal organization of the repetitive sequences, including seven microsatellite repeats and telomeric sequences (TTAGGG)n in the karyotype of the species by Fluorescence in situ Hybridization. The dinucleotide motifs had a pattern of distribution clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Concerning SSRs, we observed signals in both euchromatic and heterochromatic regions of the chromosomes, but preferably in the latter ones, as described in other vertebrate groups, such as fishes [Cioffi et al, 2011] and lizards [Pokorná et al, 2011]. In the few available studies using this approach in frogs, the SSRs have been found preferentially in the subterminal regions and secondary constrictions of chromosomes [Peixoto et al, 2015[Peixoto et al, , 2016Ernetti et al, 2020]. This pattern was also observed in our species but mostly associated with heterochromatin.…”
Section: Discussionsupporting
confidence: 87%
“…Concerning SSRs, we observed signals in both euchromatic and heterochromatic regions of the chromosomes, but preferably in the latter ones, as described in other vertebrate groups, such as fishes [Cioffi et al, 2011] and lizards [Pokorná et al, 2011]. In the few available studies using this approach in frogs, the SSRs have been found preferentially in the subterminal regions and secondary constrictions of chromosomes [Peixoto et al, 2015[Peixoto et al, , 2016Ernetti et al, 2020]. This pattern was also observed in our species but mostly associated with heterochromatin.…”
Section: Discussionsupporting
confidence: 87%
“…Although a few studies have evaluated the chromosomal organization of microsatellites in anuran species (Peixoto et al, 2015(Peixoto et al, , 2016Ernetti et al, 2019), we verified the clustered distribution pattern of these elements in the karyotypes of both P. carvalhoi and X. tropicalis, with clear evidence for the species-specific accumulation and distribution of some of these markers. The microsatellite repeats appear to have an intragenomic "life cycle" that includes (i) their birth in the respective genome, (ii) the subsequent increase in the number of repeats (by polymerase slippage), representing "adulthood, " and (iii) death, when the locus degrades the number of repeats by substitutions or inserts/deletions, causing the interruption of the repetitive units (Charlesworth et al, 1994;Kelkar et al, 2020).…”
Section: Pipa Carvalhoisupporting
confidence: 64%
“…Usually, microsatellites accumulations were demonstrated in the terminal regions of vertebrate chromosomes, which seems to be a common feature due to different mechanisms that accumulate these sequences in these regions ( Pokorná et al ., 2011b ; Torres et al ., 2011 ; Ruiz-Ruano et al ., 2015 ; Ernetti et al ., 2019 ; Lee et al ., 2019 ; Viana et al ., 2020 ). The (CA) n , (GA) n , (CAG) n and (GATA) n microsatellites were reported for the first time in sea turtle’s karyotypes and demonstrated that most of them possibly make up part of the repetitive units of heterochromatin in C. mydas, C. caretta , L. olivacea and E. imbricata , especially in mc.…”
Section: Discussionmentioning
confidence: 99%